Eusébio de Cesareia e a defesa do patrimônio imobiliário cristão (século IV d.C.) - Silva, Eliton Almeida da [UNESP] (2015)
This research aims to demonstrate the Eusebius effort of defending the Christian patrimony (c 260 AD -. 339 AD) during the rule of the Emperor Constantine I (313 AD - 337 AD), especially in Palestine. It was in Caesarea - capital of this Roman province - where Eusebius ruled as a Bishop in the beginning of the fourth century and penned his literary works. Caesarea is considered culturally and socially heterogeneous, in this period, having strong presence of Christians and non-Christians people (like Jews and Samaritans). It was precisely this heterogeneity that prevented the dominance of any ethnic-cultural group over another, and put its leaders in opposition - Christian and non-Christian groups. After reading Ecclesiastical History, Praise of Constantine and Life of Constantine, all of it penned by Eusebius, and considering the socio-cultural conditions of Caesarea's city and its region, we understand that Eusebius felt the need to seek an approach with the Emperor Constantine, in order for both to ensure Christian religion favouritism and strengthening for its position as representative of Christianity in his region. Another important aspect that emerges from attempts to understand the meanings of Eusebius' action is related to a difficult of locating the position of Eusebius before the multiplicity of Christianities in his historical context. Researchers have used wonder themselves: would be Eusebius orthodox or hetedorox? We understand that a defence of a fixed theological position, building orthodoxy, is less important to Eusebius than seek a balance between the numerous existing models of Christianity of this period. To do so, Eusebius rely on the actions of Constantine that seems consider him as his ally in the search of building consensus inside the Roman Empire. Besides the works of Eusebius himself, we intend to confirm our hypothesis and objectives outlined in this dissertation using the Prayer to The Assembly of The...